2015
DOI: 10.1007/s10847-015-0517-8
|View full text |Cite
|
Sign up to set email alerts
|

Self assembled macrobicycle and tricycle cages containing pyrrole rings by dynamic covalent chemistry method

Abstract: Synthesis of discrete macrobicycle and oligocycle molecules with three dimensional cavities in high yields remains very important because of their potential applications in the area of molecular recognition. Dynamic covalent chemistry method has effectively been used to synthesize such molecules. The Schiff base condensation reaction between tris(a-formylpyrrolyl-a 0 -methyl)amine and ethylenediamine readily afforded the large size [2 ? 3] macrobicycle in very high yield. The analogous reaction between this tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…118122 In some cases, more than one anion is bound within a cage produced via DCC. One example comes from Jana et al 123 who reported the synthesis and structural characterization of macrobicycles and macrotricycles obtained via Schiff base condensations. The solid state structure of the chloride anion complex of the macrobicycle 83 in the protonated form revealed that the eight amine nitrogen atoms of the neutral bicycle molecule including the two bridgehead nitrogen atoms are fully protonated.…”
Section: Bicyclic Anion Receptorsmentioning
confidence: 99%
“…118122 In some cases, more than one anion is bound within a cage produced via DCC. One example comes from Jana et al 123 who reported the synthesis and structural characterization of macrobicycles and macrotricycles obtained via Schiff base condensations. The solid state structure of the chloride anion complex of the macrobicycle 83 in the protonated form revealed that the eight amine nitrogen atoms of the neutral bicycle molecule including the two bridgehead nitrogen atoms are fully protonated.…”
Section: Bicyclic Anion Receptorsmentioning
confidence: 99%
“…Starting in 2011, Mani et al reported a series of cages, compounds 9 – 14 given in Chart , which were seen capable of binding a number of representative anions (e.g., F – , Cl – , Br – , NO 3 – , H 2 PO 4 – , and HSO 4 – ) in organic media such as CDCl 3 , DMSO- d 6 , and (CD 3 ) 2 CO under ambient conditions. A few representative X-ray structures of the resulting anion-bound cryptates are shown in Figure .…”
Section: Covalent Oligopyrrolic Macrobicyclic Cagesmentioning
confidence: 99%
“…method. [26] The Schiff-base condensation reaction between tris(α-formylpyrrolyl-α'-methyl)amine 40 and ethylenediamine readily gave thermodynamically stable 41. Subsequent reduction reaction using sodium borohydride yielded corresponding saturated product 42 (Scheme 10).…”
Section: N Bridgeheadsmentioning
confidence: 99%
“…Mani and co-workers reported a large size macrobicycle 41 and its reduced product 42 by dynamic covalent chemistry (DCC) method. [26] The Schiff-base condensation reaction between tris(α-formylpyrrolyl-α'-methyl)amine 40 and ethylenediamine readily gave thermodynamically stable 41. Subsequent reduc- tion reaction using sodium borohydride yielded corresponding saturated product 42 (Scheme 10).…”
Section: N Bridgeheadsmentioning
confidence: 99%
See 1 more Smart Citation